Gender differences in the effects of urban environment on nighttime exercise behaviours: a qualitative study - Su, Yuqin; Pan, Xiaoli; Li, Yike; Li, Guanchong; Zhang, Guodong (Frontiers in Psychology, 2024)
Objective: With the acceleration of urbanization, nighttime exercise behaviours have rapidly emerged. Existing research indicates a correlation between urban environments and physical activity; however, studies focusing specifically on nighttime are still insufficient, particularly regarding gender differences. This study aims to identify the key factors in urban environments that influence residents' nighttime exercise behaviours and to explore the gender differences within these influences.Methods: Purposeful sampling was employed to conduct semi-structured interviews with 30 residents who regularly engage in nighttime exercise. All transcribed interviews were analyzed using Colaizzi's phenomenological data analysis method.The findings revealed that physical environment and environmental perception are the two primary factors influencing nighttime exercise behaviour.These factors are further divided into ten specific sub-themes: lighting, green spaces, site facilities and layout, traffic coherence, entertainment facilities, smart sports equipment, sense of safety, convenience, pleasure, and sense of belonging.Females demonstrate a heightened sensitivity to the perception of the physical environment, placing greater emphasis on the feelings and experiences it provides. Males, on the other hand, focus more on the direct impact of the physical environment, such as its specific effects on exercise performance. Future urban planning and public policy should give greater consideration to gender differences in the use of urban exercise facilities, ensuring that nighttime exercise environments meet the needs of residents of different genders. This approach will contribute to enhancing overall community vitality and improving residents' health.